Japan’s Exports of Creative Goods: Current Challenges and State Policy - G. D. Paksiutov (Мир новой экономики, 2021)
For the last two or three decades, concepts such as ‘creative industries’ and ‘creative economy’ have become widely recognized and influential in both academic literature and business practice. Creative industries are believed to be a key engine of economic growth in the current era. In Japan, development of the nation’s creative industries is an essential priority of the state, and various measures aimed at achieving this goal have been implemented, which are often collectively referred to as ‘Cool Japan’ strategy. It is assumed that cultural and creative industries present Japan with a possibility to revitalize the national economy after the long period of unsatisfactory performance known as ‘the Lost Decade’ and to strengthen the country’s position on the global political arena. There are numerous academic studies dedicated to the analysis of ‘Cool Japan’ strategy and the accession of Japan’s creative industries’ performance. The authors of these studies, who are often sceptical of ‘Cool Japan’ strategy, highlight several factors hindering Japanese creative exports, such as insufficient international marketing efforts and underdeveloped international distribution networks. Furthermore, it is asserted that Japanese creative exports are restricted by the Japanese content producers’ hesitation to switch to digital technologies and by their focus on catering to the domestic market (‘Galapagos syndrome’). Collaboration between Japanese animation producers and Netflix is a notable exception. National creative industries policy could play an important role in overcoming of all challenges mentioned above.